Light-driven conductivity in Quasi-one-dimensional charge density wave insulator (TaSe4)2I - Zhenyang Xiao; Junqinq Guo; Guangjian Liu; Jiaren Yuan; Xiaxia Liao; Yangbo Zhou (iScience)
Summary: Charge density waves (CDWs) represent a fundamental phenomenon in condensed matter physics with profound implications for quantum materials research. Here, we present a systematic investigation of light-driven transport properties in quasi-one-dimensional (TaSe4)2I nanoribbons at cryogenic temperatures. We demonstrate a pronounced photocurrent response below 80 K, which induces a transition from the CDW-stabilized insulating state to a conductive state. Remarkably, the generated photocurrent exhibits a broadband response behavior from 450 nm to 1,550 nm, with a polarization selectivity and fast response time (<100 μs). Such unconventional optoelectronic response can be attributed to the existence of the CDW gap with modulations to structural incommensurability under light illumination. Our findings enhance the fundamental understanding of CDW systems, while establishing promising avenues for developing advanced optoelectronic technologies.